Brain Behavior in Learning and Memory Recall Process: A High-Resolution EEG Analysis - Amin, Hafeez Ullah; Malik, Aamir Saeed; Badruddin, Nasreen; Chooi, Weng-Tink (2013)
Learning is a cognitive process, which leads to create new memory. Today, multimedia contents are common-ly used in classroom for learning. This study investigated brain physiological behavior during learning and memory process using multimedia contents and Electroencephalogram (EEG) method. Fifteen healthy subjects voluntarily participated and performed three experimental tasks: i) Intelligence task, ii) learning task, and iii) recall task. EEG was recorded duration learning and memory recall task using 128 channels Hydro Cel Geodesic Net system (EGI Inc., USA) with recommended specifications. EEG source localization showed that deep brain medial temporal region was highly activated during learning task. EEG theta band in frontal and parietal regions and gamma band at left posterior temporal and frontal regions differentiated successful memory recall. This study provides additional understanding of successful memory recall that complements earlier brain mapping studies.